Determination of Employee Performance: Analysis of Leadership, Competence, and Discipline through Employee Retention - Sismiati Sismiati; Syarifuddin Sulaiman; Andi Muhammad Rudhan; Nurlela Nurlela; Yosef Dema; Iwan Darmawansyah; Rizal Rahmawan; Hageem Che-Ni (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This literature review aims to develop hypotheses for future research regarding the factors that influence employee performance in the public sector. The article, titled "Determination of Employee Performance: Analysis of Leadership, Competence, and Discipline through Employee Retention," adopts a comparative analysis approach by reviewing 53 relevant studies published within the last eight years. The data sources include reputable academic databases such as Scopus, Web of Science, Elsevier, Springer, SAGE, Emerald, DOAJ, EBSCO, and SINTA 2–5 journals. The findings of the literature review reveal that: (1) Leadership, competence, and discipline significantly influence employee retention; (2) These three variables also have a direct impact on employee performance; and (3) Employee retention mediates the relationship between leadership, competence, and discipline with employee performance. The study The study provides a conceptual framework that highlights the importance of human resource management strategies that integrate these key variables to enhance employee performance in public organizations